A case report of abdominal sponge in ileum in a patient with intestinal obstruction - Ammar , Ahmed Siddique (Journal of the Pakistan Medical Association, 2020)
Abstract A 36-year-old woman presented in the emergency department of East Surgical Ward of MAYO Hospital Lahore, Pakistan, in August 2019 with compliant of abdominal pain and vomiting for the past five days. The patient had a history of three Caesarean sections, the last one three years back. Off and on, she experienced abdominal pain and distension which was relieved after taking local medicines. She had no comorbid conditions and her baseline investigations were normal. On examination she had tachycardia with pulse 110/min and her whole abdomen was tender with exaggerated bowel sounds. X ray of the abdomen showed multiple air fluid levels in the small intestine. Exploration plan was made; a distended segment of ileum was later found to have abdominal sponge inside its lumen. Continuous...